Analisis Peramalan Penjualan Minuman Sari Nanas Segarrr pada PT Putra Jaya Nanas di Kabupaten Blitar, Provinsi Jawa Timur - NURUL SOLEKAH; I GUSTI AGUNG AYU AMBARAWATI; NI MADE CLASSIA SUKENDAR (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis of Forecasting drink Sales of Sari Nanas Segarrr at PT Putra Jaya Nanas in Blitar Regency, East Java Province. PT Putra Jaya Nanas is a company that processes pineapples into beverage product. The sale of Sari Nanas Segarrr beverage had fluctuated from May 2017 to May 2020 due to seasonal factor. This study aims to determine the best method of forecasting sales for Sari Nanas Segarrr and analyze the sale forecasting level in the upcoming period using the best forecasting method. This study uses 37 months sales data from May 2017 to May 2020. The sales data are processed using a time series forecasting method to select the best method by looking at the value of the Mean Squared Error (MSE). Based on the analysis, the best forecasting method is the Quadratic Trend (non- linear) method which has the smallest MSE. The forecasting method suggests that the next year sales, from June 2020 to May 2021 (period 38 – 49), will increase with the average monthly sales of 9, 09%. The company should use the forecasting method for better stock planning and to optimize the production in meeting the demand in the coming year.